The Relationship Between Gratitude and Happiness Among Students of HKBP Nommensen University - Kevin Budianto Siregar; Nenny Ika Putri (Utan Kayu Publishing, 2026)
This study was conducted to examine the relationship between gratitude and happiness among students at HKBP Nommensen University. The method used in this study was a quantitative approach. The subjects of this research were 212 students of HKBP Nommensen University selected using a random sampling technique. The measurement instruments applied in this study were the Gratitude Scale and the Happiness Scale, which employed a Likert scale with a score range of 1–5. The data analysis technique used was Pearson’s product-moment correlation with a significance level of 5%. Based on the data analysis, the correlation coefficient obtained was r = 0.393 with a significance value of 0.000 (p 0.005). These findings suggest a significant relationship between gratitude and happiness, indicating that higher levels of gratitude are associated with greater happiness, and conversely, lower levels of gratitude correspond to lower levels of happiness.